KUCHSIZ YAQINLASHISH USULIDAN FOYDALANIB BYURGERS TIPIDAGI BIR O‘LCHOVLI TENGLAMALAR SISTEMASI YECHIMINING MAVJUDLIGI VA YAGONALIGINI ISBOTLASH - Uzoqov, Z.U.; Turdiev, U.Q. (SCIENCE and SOCIETY, 2024)
The Koshi problem for a one-dimensional system of Byurgers type equations arising in two-velocity hydrodynamics is considered. By the method of weak approximation, the existence and uniqueness of the solution of the Koshi problem for a one-dimensional Byurgers type system is proved.
Keywords: two-velocity hydrodynamics; Byurgers type system; weak approximation method